2020
DOI: 10.1108/ijwhm-08-2020-0137
|View full text |Cite
|
Sign up to set email alerts
|

Online resources supporting workers with chronic episodic disabilities: an environmental scan

Abstract: PurposeThe purpose of this research was to conduct an environmental scan describing publicly available resources focussed on working with an episodic disability and providing information and advice about communication and accommodation to support working people living with episodic disabilities.Design/methodology/approachThe authors conducted an environmental scan of English language, freely available, online resources relevant to episodic disabilities in the workplace. The authors used Google™ to conduct stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Further research is required to better understand whether interventions or programs to improve aspects of workplace culture are effective in the accommodation of various episodic conditions. Recent research exploring available resources for episodic health conditions reveal similar types of accommodations and supports described among available resources (Van Eerd et al, 2020).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Further research is required to better understand whether interventions or programs to improve aspects of workplace culture are effective in the accommodation of various episodic conditions. Recent research exploring available resources for episodic health conditions reveal similar types of accommodations and supports described among available resources (Van Eerd et al, 2020).…”
Section: Discussionmentioning
confidence: 97%
“…In addition, there are a number of episodic physical and mental health conditions that have intermittent symptoms and are largely invisible to others, which could benefit from the types of accommodations described in this study on depression (e.g., Inflammatory Bowel Disease, anxiety disorders). Ongoing research by members of our team have revealed the need for similar accommodations and concomitant challenges in implementing such accommodations (Gignac et al, 2021a;Gignac et al, 2021b;Van Eerd et al, 2020). Workplace parties often consider workplace culture to be an important element in the accommodation of episodic health conditions (Corbière et al, 2016;Corbière et al, 2014;Gignac et al, 2021a).…”
Section: Discussionmentioning
confidence: 99%
“…[International Labor organization (ILO,2020) [9] in her recently published guide policy titled covid-19 and new meaning of safety and health at work suggested constant labour inspection policy system a means of reducing work hazard. But work of (Dwayne et al ,2020) [6] and (Guilhermef, 2021) [8] opposed the views of (I LO, 2020) and [Benjamin, 2021] that supports face-to-face working condition with the introduction of fourth industrial resolution technology that eliminates disruption in production and distribution in the industries by introduction of artificial intelligence in the covid-19 era and thus lowering risk of infections.…”
Section: Related Studymentioning
confidence: 99%
“…At the same time, legislation in many countries protects workers with disabilities from discrimination, including workers with mental health conditions. Mental health awareness campaigns have shed greater light on the stigma experienced by individuals and offer education and skills building for workplaces [ 34 ]. This could mean that workers who disclose their mental health condition have comparable outcomes to workers with physical health conditions.…”
Section: Introductionmentioning
confidence: 99%